The Religious Multicultural Value in the Religiosity Experiences Found in Husni Djamaluddin's Poetries - Muliadi Sam (Humaniora, 2017)
Poetry is a literal work representing action and thought of the poet after interacting with both inner worlds, his/her thought, and outer worlds, phenomena. This research attempted to deliver an idea about a model of multicultural study by utilising the poetry texts as the data source. The research scope was limited to religious multicultural values; (1) personal freedom, (2) sacriﬁce, and (3) uncontrolled sexual desire (adultery). Multicultural is one way to understand the diversity. There is a connection between the religiosity and divinity. Being religious is also about how human communicates with their creator, God. This research was a qualitative where the data were words, lines, and paragraphs in the chosen poetries. The data were subjected to analysis of Ricoeur hermeneutic approach. Husni Djamaluddin asserted that that freedom is always bonded with obligation. Sacriﬁce refers to the essence of kindness and greatness of all creatures. The awareness of each individual as the organic part of the society that must obey the customary law, religion law, and national law is the main key to prevent the uncontrolled lust release in the community.